Legal Implications of Financial Technology in Emerging Markets - Hasnah Aziz; Agustine Susi Mulyati; Donny Ferdiansyah; Muhammad Ali Mustofa; Toyib Zainal (Cita Konsultindo Research Center, 2026)
The rapid growth of financial technology (fintech) has transformed the structure and delivery of financial services in the digital economy. This paper examines the evolving legal landscape governing fintech, highlighting key regulatory challenges and emerging opportunities. It explores how innovations such as digital payments, peer-to-peer lending, and blockchain-based systems disrupt traditional financial frameworks, creating gaps in existing legal regimes. The study analyzes issues related to consumer protection, data privacy, cybersecurity, and cross-border transactions, emphasizing the need for adaptive and harmonized regulations. Furthermore, it discusses the role of regulatory bodies in balancing innovation with risk mitigation to ensure financial stability. By reviewing comparative regulatory approaches across jurisdictions, this paper identifies best practices and policy recommendations for effective fintech governance. The findings suggest that a flexible, technology-neutral, and collaborative regulatory framework is essential to foster innovation while safeguarding public interests in the increasingly interconnected global financial system.